Food in society : economy, culture, geography - Atkins, P. J. [ (Peter J.)]; Bowler, Ian R. (Hodder Education, 2007)
A geographical overview of today's dominant food system - one developed in and controlled by northern industrialized countries, and one that is becoming increasingly globalized. It provides an introduction to food studies, synthesizing literature from different disciplines